2017
DOI: 10.1073/pnas.1700694114
|View full text |Cite
|
Sign up to set email alerts
|

G9a coordinates with the RPA complex to promote DNA damage repair and cell survival

Abstract: Histone methyltransferase G9a has critical roles in promoting cancercell growth and gene suppression, but whether it is also associated with the DNA damage response is rarely studied. Here, we report that loss of G9a impairs DNA damage repair and enhances the sensitivity of cancer cells to radiation and chemotherapeutics. In response to DNA double-strand breaks (DSBs), G9a is phosphorylated at serine 211 by casein kinase 2 (CK2) and recruited to chromatin. The chromatin-enriched G9a can then directly interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 68 publications
4
53
0
1
Order By: Relevance
“…The WIZ interacting partner G9a has been reported to directly interact with and is crucial for chromatin recruitment of RPA to damage sites ( Yang et al, 2017 ), which activates the ATR-CHK1 axis of DNA damage response. We examined the sensitivity of WIZ-KO cells with hydroxyurea (HU), ATR inhibitor (ATRi; AZD6738), CHK1 inhibitor (CHKi; LY2606368), and PARP inhibitor (PARPi; olaparib) ( Figures S6E-S6H ).…”
Section: Resultsmentioning
confidence: 99%
“…The WIZ interacting partner G9a has been reported to directly interact with and is crucial for chromatin recruitment of RPA to damage sites ( Yang et al, 2017 ), which activates the ATR-CHK1 axis of DNA damage response. We examined the sensitivity of WIZ-KO cells with hydroxyurea (HU), ATR inhibitor (ATRi; AZD6738), CHK1 inhibitor (CHKi; LY2606368), and PARP inhibitor (PARPi; olaparib) ( Figures S6E-S6H ).…”
Section: Resultsmentioning
confidence: 99%
“…Laser micro-irradiation was performed as previously descried. 63 Briefly, cells were grown on a glass-bottomed dish and locally irradiated with a 365 nm pulsed nitrogen UV laser (16 Hz pulse, 41% laser output) generated from a micropoint system (Andor). This system was directly coupled to the epifluorescence path of the Nikon A1 confocal imaging system and time-lapse images were captured every 10 s for the indicated time.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, among the candidate lysine methyltransferases regulating MDC1 in DDR, EHMT1 [also known as G9A-like protein; GLP or KMT1D (lysine methyltransferase 1D)] and EHMT2 [also known as G9A or KMT1C (lysine methyltransferase 1C)] were identified as mediators for the proper methylation of MDC1. Interestingly, recent studies have shown that EHMT2 7 and its catalytic activity 8 , 9 promote DNA repair in response to DSB-inducing genotoxic stress. However, the precise mechanism of EHMT2 linked to EHMT1 in DDR remain elusive.…”
Section: Introductionmentioning
confidence: 99%